Strategi Pengembangan Budaya Organisasi untuk Meningkatkan Daya Saing Perusahaan - Gunawan, Nadia; Hasibuan, Wildan Anshori; Sinaga, Eli Timo; Solin, Tania Kunata (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze organizational culture development strategies in enhancing company competitiveness. The research employs a qualitative method with a case study approach on a manufacturing company in Indonesia. Data were collected through in-depth interviews, observations, and documentation to understand the implementation of organizational culture strategies. The results show that the application of company values, effective communication, and active employee engagement can strengthen an adaptive and innovative organizational culture. This positively impacts productivity, employee loyalty, and the company's competitive advantage in the market.